Pengaruh Edukasi Postpartum dengan Metode Family Centered Maternity Care Terhadap Dukungan Keluarga dalam Pemberian ASI - Winarti, Gusti (Jurnal Pustaka Keperawatan (Pusat Akses kajian Keperawatan), 2026)
The postpartum period is a crucial phase for mothers as it involves physiological and psychological changes that require adjustment to their new role as parents. Family support plays a significant role in the success of breastfeeding, encompassing informational, emotional, instrumental, and appraisal support. This study aims to analyze the effect of postpartum education based on Family Centered Maternity Care (FCMC) on family support in breastfeeding. The research design employed a quasi-experimental method with a pretest and posttest control group approach. The study population consisted of pregnant women without complications at 36–40 weeks of gestation in the working area of UPT Puskesmas Kampung Baru. A total of 52 respondents were selected, divided into an intervention group (26 participants) and a control group (26 participants) using consecutive sampling techniques. Data analysis was conducted using Paired T-Test and Independent T-Test. The results showed that FCMC-based education effectively increased family support (p = 0.000; p < 0.05). In conclusion, FCMC-based education is proven to strengthen family support for postpartum mothers, thereby contributing to the success of exclusive breastfeeding.